(untitled) (Baghdad Science Journal, 2021)
This research focuses on the characteristics of polyvinyl alcohol and starch polymer blends doping with Rhodamine-B. The polymer blends were prepared using the solution cast method, which comprises 1:1(wt. /wt.). The polymer blends of PVA and starch with had different ratios of glycerin 0, 25, 30, 35, and 40 % wt. The ratio of 30% wt of glycerin was found to be the most suitable mechanical properties by strength and elasticity. The polymer blend of 1:1 wt ratios of starch/PVA and 30% wt of glycerin were doped with different ratios of Rhoda mine-B dye 0, 1, 2, 3, 4, 5, and 6% wt and the electrical properties of doping biodegradable blends were studied. The ratio of Rhodamine-B 5% wt to the polymer blends showed high conductivity up to 1×10-3. In general, the electrical conductivity was increased with high temperature, which is similar to the behavior of semi-conductive polymers. This work focuses on the characteristics of polymer blend based on starch and polyvinyl alcohol doping with Rhodamine-B. the polymer blends were prepared using the solution cast method, which comprising 1:1(wt./wt.). ratio starch and polyvinyl alcohol and different ratio of glycerin (0, 25, 30, 35,and 40) %. The ratio of 30% of glycerin was found to be the most suitable mechanical properties. The polymer blend of 1:1 starch/PVA and 30%of glycerin were doped with different ratio of Rhoda mine-B dye (0, 1, 2, 3, 4, 5, and 6%) and the electrical properties of doping biodegradable blends were studied. The ratio of Rhodamine-B 5% to the polymer blends was high conductivity up to 1×10-3. In general, the electrical conductivity was increased with high temperature this is similar to the behavior of semi-conductive polymers. This work focuses on the characteristics of polymer blend based on starch and polyvinyl alcohol doping with Rhodamine-B. the polymer blends were prepared using the solution cast method, which comprising 1:1(wt./wt.). ratio starch and polyvinyl alcohol and different ratio of glycerin (0, 25, 30, 35,and 40) %. The ratio of 30% of glycerin was found to be the most suitable mechanical properties. The polymer blend of 1:1 starch/PVA and 30%of glycerin were doped with different ratio of Rhoda mine-B dye (0, 1, 2, 3, 4, 5, and 6%) and the electrical properties of doping biodegradable blends were studied. The ratio of Rhodamine-B 5% to the polymer blends was high conductivity up to 1×10-3. In general, the electrical conductivity was increased with high temperature this is similar to the behavior of semi-conductive polymers.